The Neonatal Development of Intraepithelial and Lamina Propria Lymphocytes in the Murine Small Intestine - Steege, Jessica C. A. Ter (Hindawi Publishing Corporation, 1997)
During early neonatal life, important changes occur in the gut. The intestine is challenged by both milk and a microbial flora. Later on, at weaning, the diet of mice changes from milk to pelleted food leading to changes in microbial contents. This period seems essential for a complete development of the mucosal immune system. We investigated the development of both intraepithelial (IEL) and lamina propria lymphocytes (LPL), from day 5, and every 5 days, up to day 30 after birth. IEL and LPL were isolated from the small intestine and the phenotype was assessed by FACS analyses, using antibodies for detection of T-cell markers CD3, TCRαβ, TCRγδ, CD4, CD8α, CD8β, CD5, CD18, CD54, and CD49d. Our data show a clear increase in the number of LPL just before weaning, while the number of IEL increased after day 15. A more mature pattern of membrane antigen expression of both IEL and LPL was observed at weaning. The adhesion molecules CD18, CD54, and CD49d, essential for cellular communication of lymphocytes, showed an expression peak at weaning. In conclusion, the mouse mucosal immune system develops during the first 3 weeks of neonatal life leading to the formation of a more mature immune system at weaning.